Analisis Pengaruh Labelisasi Halal, Harga Dan Desain Kemasan Terhadap Pembelian Mie Instan Impor - Vita Sarasi; Arief Helmi; Andry Fitriani Burhanudin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine how the influence of packaging design, halal labels, and prices on the purchase decision of imported instant noodles. The research method used was quantitative in the form of distributing questionnaires using a purposive sampling technique to 160 Muslim students at various universities in the city of Bandung. Data collection was carried out using Google Forms and processed using SEM-PLS. The results of the study show that packaging design, halal labels, and prices have a positive and significant effect on the purchase decision of imported instant noodles. Imported instant noodle producers are expected to pay more attention to these three factors in their marketing techniques. The public is also demanded to be wiser in choosing imported instant noodle products because not all of them are labeled as halal, have informative packaging, and are affordable prices. Further researchers are advised to add other variables that have an influence on purchasing decisions.